2014
DOI: 10.4236/ojog.2014.41001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting adverse maternal and perinatal outcome after threatened miscarriage

Abstract: Objectives: Threatened miscarriage is the most common complication of pregnancy, occurring in 20%-25% of ongoing pregnancies. The purpose is to study maternal and perinatal outcome in women with threatened miscarriage. Methods: A prospective study was conducted over a period of 20 months in the Department of Obstetrics and Gynaecology, Pannadhay Mahila Chikitsalaya, a tertiary care center in Udaipur, India. It included a cohort of pregnant patients with a history of threatened miscarriage during the first twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
(51 reference statements)
5
23
1
1
Order By: Relevance
“…A previous study done by Agarwal et al found an incidence of 21% in 62 patients with a history of threatened abortion in first twenty weeks of pregnancy. 9 Another study by Ahmed et al showed the incidence of abortion in 85 patients with bleeding in first twenty weeks of pregnancy to be 17%. 10 The lower rate of abortion in our study could be attributed to the fact that we have included only first trimester threatened abortion.…”
Section: Abortionmentioning
confidence: 99%
“…A previous study done by Agarwal et al found an incidence of 21% in 62 patients with a history of threatened abortion in first twenty weeks of pregnancy. 9 Another study by Ahmed et al showed the incidence of abortion in 85 patients with bleeding in first twenty weeks of pregnancy to be 17%. 10 The lower rate of abortion in our study could be attributed to the fact that we have included only first trimester threatened abortion.…”
Section: Abortionmentioning
confidence: 99%
“…later in pregnancy causing adverse outcomes such as increased risk of pre-eclamptic toxemias, preterm delivery, prelabour rupture of membranes(PROM), and IUGR. 3 The purpose of this study was to investigate the effect of first trimester vaginal bleeding on maternal and perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of fetal loss reported varies among studies due to the fact that many studies are retrospective, of small sample size or relied on patients recall recruiting later in pregnancy. Agrawal S and colleagues (2014) in a small prospective case control study found the overall spontaneous miscarriage rate for patients after diagnosis of a viable pregnancy by ultrasound as 21% for cases versus 5.45% for control group [12].…”
Section: Discussionmentioning
confidence: 99%